Social reward improves the voluntary control over localized brain activity in fMRI-based neurofeedback training - Mathiak, Krystyna A.; Alawi, Eliza M.; Koush, Yury; Dyck, Miriam; Cordes, Julia S.; Gaber, Tilman J.; Zepf, Florian D.; Palomero-Gallagher, Nicola; Sarkheil, Pegah; Bergert, Susanne; Zvyagintsev, Mikhail; Mathiak, Klaus (Frontiers in Behavioral Neuroscience, 2015)
Neurofeedback (NF) based on real-time functional magnetic resonance imaging (rt-fMRI) allows voluntary regulation of the activity in a selected brain region. For the training of this regulation, a well-designed feedback system is required. Social reward may serve as an effective incentive in NF paradigms, but its efficiency has not yet been tested. Therefore, we developed a social reward NF paradigm and assessed it in comparison with a typical visual NF paradigm (moving bar). We trained 24 healthy participants, on three consecutive days, to control activation in dorsal anterior cingulate cortex (ACC) with fMRI-based NF. In the social feedback group, an avatar gradually smiled when ACC activity increased, whereas in the standard feedback group, a moving bar indicated the activation level. To assess a transfer of the NF training both groups were asked to up-regulate their brain activity without receiving feedback immediately before and after the NF training (pre- and post-test). Finally, the effect of the acquired NF training on ACC function was evaluated in a cognitive interference task (Simon task) during the pre- and post-test. Social reward led to stronger activity in the ACC and reward-related areas during the NF training when compared to standard feedback. After the training, both groups were able to regulate ACC without receiving feedback, with a trend for stronger responses in the social feedback group. Moreover, despite a lack of behavioral differences, significant higher ACC activations emerged in the cognitive interference task, reflecting a stronger generalization of the NF training on cognitive interference processing after social feedback. Social reward can increase self-regulation in fMRI-based NF and strengthen its effects on neural processing in related tasks, such as cognitive interference. An advantage of social feedback is that a direct external reward is provided as in natural social interactions, opening perspectives for implicit learning.